Rivers by design : state power and the origins of U.S. flood control - O'Neill, Karen M., 1959- (E-Duke books scholarly collection., 2006)
A sociological history of flood control politics that examines how local and regional pro-growth interests organized to press the federal government to protect land from flooding, and how this action altered the relationship between regions and the federa.